Pencegahan Bullying pada Anak Usia Dini melalui Pendidikan Karakter di PAUD SKB Mojoagung - Lopa, Eliviana Berlian; Susilo, Heryanto (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
Early Childhood Education is a critical period in children's development, they experience rapid physical, cognitive, social and emotional growth. Cases of bullying also occur in early childhood. The serious impact of bullying requires the need to prevent bullying in character education. The aim of this research is to obtain a description of the implementation of character education and prevention of bullying through character education. This study used qualitative research methods. Data was collected using in-depth interview techniques, observation and documentation. Data analysis techniques are data collection, data condensation, data display, and drawing conclusions. The research results show that there is a commitment to instilling character values in students through the habituation method every day before learning begins. Preventing bullying through character education, namely the school's commitment to the formation of a Violence Prevention and Handling Team (TPPK), parenting programs, instilling moral values and directly handling bullying, teaching the values of tolerance and responsibility can create a full learning environment. love for all students.